Manajemen Sumber Daya Manusia Perspektif Islam: Strategi Membangun SDM Unggul dan Berkarakter - Sizka Farwati (JMiE (Journal of Management in Education), 2024)
Human resource management (HRM) plays a crucial role in supporting the success of educational institutions, as human resources are the key element in realizing the vision and mission of an organization. Without proper planning and standards, the potential of human resources may become an obstacle rather than a strength in achieving institutional goals. This study aims to explain the implementation of Human Resource Management (HRM) from an Islamic perspective. The research method employed is a literature review, analyzing books and previous studies using descriptive analysis. The findings indicate that: (1) HRM encompasses all processes related to planning, organizing, leading, and controlling the development and guidance of Muslim individuals within organizations optimally; (2) The internalization of Islamic values is the responsibility of Muslims to prepare superior and qualified human resources across various aspects of life; (3) Islamic educational institutions play a vital role in producing individuals with broad knowledge, strong skills, technological competence, and a foundation of faith and piety, which serve as the basis for mastering knowledge, enhancing expertise, and applying knowledge in accordance with religious, moral, and governmental regulations; (4) The Qur’an and Hadith provide normative guidance for the internalization of HRM from an Islamic perspective. This study offers a deeper understanding of HRM implementation based on Islamic values and emphasizes the importance of structured, organized, and directed processes aligned with the principles of Sharia.